Explaining the internet usage of SMEs: The impact of market orientation, behavioural norms, motivation and technology acceptance. Issue 3 (1st June 2015) - Caniëls, Marjolein C. J.; Lenaerts, Heidi K. L.; Gelderman, Cees J.
Abstract : Purpose: – Small to mid-sized enterprises (SMEs) are underrepresented in market orientation and internet-related research. Yet, marketing-related issues represent some of the most important problems for SMEs. The purpose of this paper is to explain why SMEs use the internet in business processes and to explore the relationship between market orientation and internet usage. Design/methodology/approach: – The study amalgamates the technology acceptance model, the motivation model and the integrated model of technology acceptance into one model. Hypotheses are tested with survey data from Belgian SMEs using partial least squares. Findings: – One of the findings is that intrinsic and extrinsic motivation are positively significantly related to internet usage intention. No significant relationships were found between behavioural norms and perceived ease of use and between perceived ease of use and the intention to use the internet. Practical implications: – Managerial implications include that SME-internet training providers should focus on methods to increase the user's perceived enjoyment (intrinsic motivation) instead of emphasizing the perceived ease of use of the internet. Originality/value: – Researchers as well as practitioners have stressed the gains from implementing market-orientated strategies in firms. Together with the prominence of studies about patterns and characteristics of internet usage, this calls for studies that integrate these two streams of literature. The study shows in what way market orientation is related to the capability to use internet to a firm's long term advantage. Up till now the relationship between market orientation and internet use has hardly received attention.